Analysis of ethylene biosynthesis and perception during postharvest cold storage of Marsh and Star Ruby grapefruits. (October 2015) - Lado, Joanna; Rodrigo, María Jesús; Zacarías, Lorenzo
Grapefruits are among the citrus species more sensitive to cold and develop chilling injury symptoms during prolonged postharvest storage at temperatures lower than 8 ℃–10 ℃. The plant hormone ethylene has been described either to protect or potentiate chilling injury development in citrus whereas little is known about transcriptional regulation of ethylene biosynthesis, perception and response during cold storage and how the hormone is regulating its own perception and signaling cascade. Then, the objective of the present study was to explore the transcriptional changes in the expression of ethylene biosynthesis, receptors and response genes during cold storage of the white Marsh and the red Star Ruby grapefruits. The effect of the ethylene action inhibitor, 1-MCP, was evaluated to investigate the involvement of ethylene in the regulation of the genes of its own biosynthesis and perception pathway. Ethylene production was very low at the harvest time in fruits of both varieties and experienced only minor changes during storage. By contrast, inhibition of ethylene perception by 1-MCP markedly induced ethylene production, and this increase was highly stimulated during shelf-life at 20 ℃, as well as transcription of ACS and ACO . These results support the auto-inhibitory regulation of ethylene in grapefruits, which acts mainly at the transcriptional level of ACS and ACO genes. Moreover, ethylene receptor1 and ethylene receptor3 were induced by cold while no clear role of ethylene was observed in the induction of ethylene receptors. However, ethylene appears to be implicated in the transcriptional regulation of ERFs both under cold storage and shelf-life.